Determinants of Professional Service Output Quality in the South African Construction Industry - Govender, Neil (University of the Witwatersrand, Johannesburg, 2024)
The debate regarding the relationship between fees and the quality of professional services in the construction industry has persisted since the 1980s. In the South African context, members of professional industry bodies have strongly suggested that the declining quality of professional service outputs (PSOs) in the construction industry is due to low fees. While various studies in the construction literature have asserted that low or “discounted” fees are one of the main factors influencing the quality of PSOs, other studies have rejected this assertion. However, a comprehensive investigation into the major built environment professions, aimed at identifying and evaluating various factors influencing PSO quality, as well as understanding how and to what extent quality is specifically influenced by fees, is notably absent from the construction literature. To address this gap, a three-stage research design was employed. This design included an industry-wide survey with 604 participants, a survey of nine industry experts averaging 38 years of experience, and case studies conducted with seven built environment consulting companies. The data analysis involved a combination of content analysis, descriptive analysis, and thematic analysis. The study revealed nuances in the key factors influencing PSO quality across various built environment professions. While fees were identified as a key factor influencing PSO quality, other key factors, such as the time required to produce PSOs, experience, available information, and project briefs, were also identified. This highlights the need for project stakeholders to effectively manage professional fees in conjunction with these other key factors to ensure the quality of PSOs is not diminished. The findings of this study provide both clients and professionals with the knowledge to navigate the complex interplay between fees and PSO quality, ultimately fostering more successful and efficient projects.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Fees; Quality; Professional Services; Construction Industry; SDG-9: Industry, innovation and infrastructure; SDG-11: Sustainable cities and communities